Metabolic Crisis in Severely Head-Injured Patients: Is Ischemia Just the Tip of the Iceberg? - Carre, Emilie; Ogier, Michael; Boret, Henry; Montcriol, Ambroise; Bourdon, Lionel; Risso, Jean-Jacques (Frontiers in Neurology, 2013)
Ischemia and metabolic crisis are frequent post-traumatic secondary brain insults that negatively influence outcome. Clinicians commonly mix up these two types of insults, mainly because high lactate/pyruvate ratio (LPR) is the common marker for both ischemia and metabolic crisis. However, LPR elevations during ischemia and metabolic crisis reflect two different energetic imbalances: ischemia (Type 1 LPR elevations with low oxygenation) is characterized by a drastic deprivation of energetic substrates, whereas metabolic crisis (Type 2 LPR elevations with normal or high oxygenation) is associated with profound mitochondrial dysfunction but normal supply of energetic substrates. The discrimination between ischemia and metabolic crisis is crucial because conventional recommendations against ischemia may be detrimental for patients with metabolic crisis. Multimodal monitoring, including microdialysis and brain tissue oxygen monitoring, allows such discrimination, but these techniques are not easily accessible to all head-injured patients. Thus, a new “gold standard” and adapted medical education are required to optimize the management of patients with metabolic crisis.